MODEL KINETIKA PENGERINGAN MANISAN MANGGA (Mangifera indica L.) - Tri Yulni (Agroindustrial Technology Journal, 2023)
To improve control over the drying process and the quality of the dried products, it is essential to comprehend the drying kinetics model. This study aim to find the best thin-layer drying kinetics model for box-shaped candied mangoes dried in a rotary oven. The source of the data is Rozana’s (2016) research into the moisture content and drying times of candied mangoes at 45 and 50°C in a rotating oven. The Lewis, Page, Henderson and Pabis, Logarithmic, Two Term, Two Term Exponential, Diffusion Approximation, Midilli et al., and Modified Henderson and Perry models are among the kinetic models used. The moisture ratios of mangoes collected during drying at various time intervals were used to fit drying models in order to predict the moisture ratio. The model with the highest coefficient of determination (R2), the lowest root mean square error (χ2), and the lowest root mean square error (RMSE) is the best drying kinetics model. The Midilli et al. model was determined to be the most appropriate drying model for box-shaped candied mangoes dried in a rotating oven with R2 of 0,9989, χ2 of 0,0001, and an RMSE value of 0,0074 for a temperature of 45°C; and R2 is 0,9973, χ2 is 0,0002, and RMSE is 0,0137 at 50°C. The Midilli et al. model equations obtained is MR=1,026 exp(-0,0007t1,0706)+0,0001t at 45°C and MR=1,0129exp(-0,0003t1,3568)+0,0002t at 50°C.